Access to High Quality Surgical Repair Services is a Fundamental Right of Patients with Obstetric Fistulas: A Study on Quality of Life Data in the Democratic Republic of the Congo - Paluku JL; Bartels SA; Kataliko BK; Furaha CM; Aksanti BK; Kalole BK; Kamabu EM; Lwanzo CM; Kasereka JML; Mukuku O; Tsongo ZK; Wembonyama SO; et al. (Dove Medical Press, 2024)
Justin Lussy Paluku,1,2 Susan A Bartels,3,4 Benjamin Kasereka Kataliko,2 Cathy Mufungizi Furaha,1,2 Barthelemy Kasi Aksanti,2 Benjamin Kambale Kalole,2 Eugénie Mukekulu Kamabu,5 Chrispin Musubao Lwanzo,2 Jonathan ML Kasereka,6 Olivier Mukuku,7 Zacharie Kibendelwa Tsongo,8 Stanis Okitotsho Wembonyama,9,10 Charles Wembonyama Mpoy,11 Jeannot Sihalikyolo Juakali12 1Department of Obstetrics and Gynecology, University of Goma, Goma, Democratic Republic of the Congo; 2Department of Obstetrics and Gynecology, HEAL Africa Hospital, Goma, Democratic Republic of the Congo; 3Department of Emergency Medicine, Queen's University, Kingston, Canada; 4Department of Public Health Sciences, Queen's University, Kingston, Canada; 5Department of Internal Medicine, HEAL Africa Hospital, Goma, Democratic Republic of the Congo; 6Department of Orthopedics and Trauma, HEAL Africa Hospital, Goma, Democratic Republic of the Congo; 7Department of Maternal and Child Health, High Institute of Medical Techniques, Lubumbashi, Democratic Republic of the Congo; 8Department of Internal Medicine, University of Kisangani, Kisangani, Democratic Republic of the Congo; 9Department of Pediatrics, University of Lubumbashi, Lubumbashi, Democratic Republic of the Congo; 10Department of Public Health, University of Lubumbashi, Lubumbashi, Democratic Republic of the Congo; 11Department of Obstetrics and Gynecology, University of Lubumbashi, Lubumbashi, Democratic Republic of the Congo; 12Department of Obstetrics and Gynecology, University of Kisangani, Kisangani, Democratic Republic of the CongoCorrespondence: Justin Lussy Paluku, Email justin.paluku@unigom.ac.cdPurpose: The aim of this study was to assess quality of life (QoL) using the WHOQOL-BREF questionnaire among obstetric fistula (OF) patients before and after surgical repair of OF (SROF).Methods: A longitudinal cohort study was conducted between November 2022 and October 2023 in the Democratic Republic of the Congo (DRC) among OF patients to assess their QoL before and after SROF. A systematic sampling technique was used to recruit a total of 158 OF patients. The WHOQOL-BREF questionnaire assessed general health, life experience, as well as physical, social, psychological, and environmental domains.Results: The mean age among the 158 respondents was 33.51 ± 9.63 years, and 77.85% of them lived in rural areas. In terms of surgical outcomes, 80.38% had closure of the OF with regained continence, 5.7% had closure of the OF with persistent incontinence, and 13.9% had a failed surgical repair. Overall mean QoL scores were higher after OF surgical repair (3.83, standard deviation [SD]=0.89) in comparison to pre-operative (1.58, SD=0.63) (p< 0.001). These QoL improvements included physical (mean score 66.32 post-surgery versus 28.37 before, p< 0.001), social (mean score 64.92 post-surgery versus 27.90 before, p< 0.001), psychological (mean score 68.09 post-surgery versus 21.28 before, p< 0.001), environmental (mean score 48.41 post-surgery versus 16.91 before p< 0.001), and general domains. Patients with a successful OF repair had a better QoL score than those with a closed fistula but ongoing incontinence or those for whom surgery failed to close the fistula.Conclusion: The present study showed that among OF patients, all QoL domains were impaired before surgical repair and significantly improved after surgery. Successful OF closure alleviates the consequences of OF and helps to restore patients' wellbeing. Our findings call for improved access to high-quality surgical repair services as a fundamental right for OF patients.Keywords: quality of life, obstetric fistula, surgical repair, questionnaire WHOQOL-BREF, DRC